Cytotoxic prenylated acetophenone dimers from acronychia pedunculata - Awang, Khalijah; Kouloura, E.; Halabalaki, M.; Lallemand, M.C.; Nam, S.; Jove, R.; Litaudon, M.; Hadi, A.H.; Skaltsounis, A.L. (American Chemical Society, 2012)
Three new acetophenone dimers or Acronychia-type acetophenones, acropyrone (1), acropyranol A (2), and acropyranol B (3), were isolated from the trunk bark of Acronychia pedunculata and structurally characterized, together with four known acetophenone dimers, acrovestone (4), acrovestenol (5), acrofolione A (6), and acrofolione B (7), the acetophenone monomer acronyline (8), and four furoquinoline alkaloids. The chemical structures of the new isolated compounds were elucidated unambiguously by spectroscopic data analysis. The cytotoxic activities of the isolated acetophenone dimers were evaluated against the DU145 prostate and A2058 melanoma human cancer cell lines as well as the NHDF normal cell line. Acrovestone (4) and acrovestenol (5) exhibited substantial cytotoxicity, with IC50 values of 0.38 and 2.8 μM against A2058 melanoma cells as well as 0.93 and 2.7 μM against DU145 prostate cancer cells, respectively.